Neonatal Mortality Surveillance System Evaluation, La-Nkwantanang Municipal Assembly, Greater Accra Region, Ghana, 2015-2019 - Dikena Jackson; Benedict Calys Tagoe; Donne Kofi Ameme; Charles Lwanga Noora; Basil Benduri Kaburi; Alice Sallar Adams; Ernest Kenu (Journal of Interventional Epidemiology and Public Health)
Introduction: Neonatal mortality occurs during the first 28 days of life and in Ghana, the rate is 25 per 1000 live births. Regular evaluation of disease/event surveillance systems is required to ensure they are meeting their objectives and serving the public health mission. Therefore, we evaluated the newborn mortality surveillance system's attributes and usefulness.